Learning gain in web (internet) sourced seminars versus textbook sourced seminars in postgraduate medical students - Sugat A Jawade; Lalit S Waghmare; Bhushan S Madke; Adarshlata B Singh; Swapna S Jawade (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In the past, textbook or printed material was the only source of information for medical students or post-graduate students. After the introduction of internet, knowledge can be accessed easily which is updated with various aids such as animation, videos which improve the learning efficiency. This study was conducted to compare the learning efficiency between textbook-based seminar to that of internet-based seminar in postgraduate students of the department of dermatology. MATERIALS AND METHODS: It was a non-randamized controlled study. The postgraduate students in the department of dermatology, Jawaharlal Nehru Medical college, DMIMS(DU),Sawangi (Meghe), Wardha, Maharashtra, India were divided into two equal groups by simple randomization method by flipping the coin. Totally 20 seminar topics were divided into two groups (A and B) consisting of 10 seminars in each group. Postgraduate students assigned in group A were asked to prepare seminar solely from textbooks while in group B, students were asked to prepare seminar by referring internet. Feedback form which consists of 7 points, i.e. appearance, completeness of preparation, clarity of presentation, appropriate use of audio visual aids, understanding of subject, ability to answer questions, and overall performance were filled up from faculties and postgraduate students after completion of each seminar. Pretest and post-test were filled up from postgraduate students before and after each seminar respectively. Learning gain was calculated by comparing the scores of pretest and posttest. Paired t-test was used to compare results in the group and unpaired t-test was used to compare results between the two groups. RESULTS: Faculties' feedback on overall performance was higher (4.59 ± 0.15) in web-based seminars as compared to in textbook-based seminars (3.85 ± 0.1) with significant P = 0.008. Furthermore, postgraduate students' feedback showed statistical significant value of 0.02 in web-based seminars (4.65 ± 0.06) compared to textbook-based seminars (3.2 ± 0.06). Learning gain was significantly higher in web-based seminar compared to textbook-based seminar with P = 0.02. CONCLUSION: It can be concluded that web-based learning can improve the learning efficiency in postgraduate medical students.